Production of metallic tools by ceramic moulding - a rapid tooling process - Teresa P. Duarte (2002)
The conversion of rapid prototyping modelsinto metallic tools for plastics injection using aceramic moulding process is presented. Theprocess main steps used in this experimental workwere: production of the model (by rapid prototypingor conventional techniques), conversion into asilicone mould, production of a ceramic mould bycasting a ceramic slurry that suffers a sol-gelreaction into a box, casting an alloy and finishing.Processing parameters like preheating of theceramic moulds, pouring temperature and heattreatingof the moulds have a very importantinfluence on the final characteristics of the metallictools. This work presents the influence of theabove parameters on the surface roughness,mechanical strength, dimensional changes,microstructure and capacity of details reproductionof the metallic tools.